Missing in action: Sustainable climate change adaptation evidence for animal health - Stephen, Craig; Wade, Joy (Canadian veterinary journal, 2020)
Health impacts of climate change are now inevitable. The objective of this study was to see if animal health climate change adaptation was a subject of scholarly inquiry, advice, or discussion and if there was an evidence base from which to make adaptation recommendations. A scoping review of English-language literature over the past 10 years was undertaken and the top findings related to animal health adaptation and climate change were inventoried on Google. Documents found in the search focussed predominantly on hypothesizing what hazards might occur with climate change, describing their spread or proposing possible impacts. Scant evidence was found of scholarship related to sustainable animal health climate change adaptation planning or action. Investment and attention to adaptation planning and research are needed to increase confidence in climate change recommendations in the face of continuing uncertainty about the breadth of effects on animal health and the best actions to take in preparing and responding to them.